Clinical management of borderline ovarian tumors. Issue 7 (July 2010) - Trillsch, F; Mahner, S; Ruetzel, JD; Harter, P; Ewald-Riegler, N; Jaenicke, F; du Bois, A
Borderline ovarian tumors (BOTs) are epithelial tumors of the ovaries characterized by cellular proliferation and nuclear atypia but without an infiltrative growth pattern. As they frequently affect younger patients the clinical management is complicated by considerations such as preserving fertility and reducing postoperative morbidity. Over the past several decades surgical therapy has shifted from a radical approach to more conservative treatment. There are various modes of surgery applied to the patients. All these developments have to be considered from an oncologic standpoint as BOTs represent a potentially malignant disease. Oncologic safety, as well as patients'' desires and expectations, have to be balanced to reach the most appropriate treatment for BOTs. For this reason current literature will be discussed in this review to give a thorough overview of this topic and to develop recommendations for the surgical management of these patients. Open questions will be identified to elaborate the need for future surveys and research.